A relação entre democracia e direitos e garantias fundamentais - Vinci, Luciana Vieira Dallaqua (2017)
Long time, democracy is object of study, not only in Brazil, but all over the world. The same can be said about fundamental rights and guarantees. However what has not been translated yet into major academic research is precisely the relationship between democracy and fundamental rights. In this way, the present work seeks to analyze the main elements of democracy and its relation with fundamental rights. In this work it will be study whether the respect for fundamental rights occurs only in a democratic regime, or whether it is possible to speak of fundamental rights in totalitarian regimes. Equally, it is an object of study to know whether the relationship between democracy and fundamental rights and guarantees is translated as something indispensable, merely desirable or even irrelevant